VD_FINDINFO Décision / 2015 / 514 vom 18. Mai 2015 - VD Tribunal cantonal (2015)
RELIEF, FORCE MAJEURE, REJET DE LA DEMANDE, JUGEMENT PAR DÉFAUT | 407 al. 1 CPP, 393 al. 1 let. b CPP (CH), 452 al. 2 CPP (CH)